ONLINE MEDIA MONITORING AND EVALUATION: COMPARATIVE APPROACHES - Saadat Abdullayeva (Problems of Information Society)
In a globalizing information society, the development of mechanisms for more efficient use of online media resources is increasingly important. Such mechanisms are significant for the effective management of information flows, formation of public opinion and safeguarding of national information security. In terms of digital transformation, the rapid dissemination and constant evolution of media content require continuous monitoring and evaluation. In this context, monitoring of media resources plays a significant role in identifying the social situation of society, public opinion trends, as well as political and economic dynamics of a country. The article explores the technological capabilities and functional advantages of modern tools used for monitoring online media resources, including automated monitoring systems. It also examines existing conceptual and methodological approaches to monitoring online media, and assesses their areas of application and effectiveness. Furthermore, the article provides insight into the capabilities of online media monitoring systems, and presents the structural components of the monitoring system, which include the collection, processing, classification and visualization of data for systematic information analysis. The article also reviews measures undertaken to improve the media environment in Azerbaijan and enhance its competitiveness, alongside legislative framework. Taking into account international experience, the article proposes the establishment of a monitoring center for assessing online media activities in Azerbaijan and gives recommendations regarding the activity and potential capabilities of this center.